2001
DOI: 10.1034/j.1600-0668.2001.110406.x
|View full text |Cite
|
Sign up to set email alerts
|

Sorptive Interactions between VOCs and Indoor Materials

Abstract: /npsi/ctrl?lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?lang=fr Access and use of this website and the material on it are subject to the Terms and Conditions set forth at http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=en NRC Publications Archive Archives des publications du CNRCThis publication could be one of several versions: author's original, accepted manuscript or the publisher's version. / La version de cette publication peut être l'une des suivantes : la version prépubli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
96
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(105 citation statements)
references
References 2 publications
5
96
2
Order By: Relevance
“…The importance of these surfaces with respect to sorption is expected to depend on the type of fabric and the presence of backing materials. For example, carpet with an underlying polyurethane foam carpet cushion, has been shown to be much more important with respect to sorption of VOCs than carpet alone and or other indoor materials (Won et al, 2000(Won et al, , 2001.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of these surfaces with respect to sorption is expected to depend on the type of fabric and the presence of backing materials. For example, carpet with an underlying polyurethane foam carpet cushion, has been shown to be much more important with respect to sorption of VOCs than carpet alone and or other indoor materials (Won et al, 2000(Won et al, , 2001.…”
Section: Discussionmentioning
confidence: 99%
“…The data have been fit to equations to obtain key parameter values, yielding semi-empirical sorption models. In an extensive study, Won et al (2001) measured adsorption and desorption rate coefficients for eight VOCs interacting with gypsum wallboard, carpet and cushion, acoustic ceiling tile, wood flooring, vinyl flooring, and fiberglass.…”
Section: Introductionmentioning
confidence: 99%
“…In order to illustrate the use of our model, we used available data for wallboard to define a fugacity capacity as well as the diffusive transfer rates between the air and the wallboard (Tichenor et al 1991;Van Loy et al 2001 ;Won et al 2001). Much of the available experimental work provides information to establish sorption and desoprtion rates from a surface.…”
Section: Resultsmentioning
confidence: 99%
“…Some have developed isotherms to model the partitioning into a surface (Jorgensen et al 2000). But it has not been established whether a chemical partitions primarily onto the surface of a material (Won et al 2001), or whether the compounds diffuse into the pores and/or body of the material (Cox et al 2001). Additionally, partitioning and diffusion may occur on different time scales, with short-term experiments accounting for partitioning onto the surface and long term experiments accounting for diffusion into the material.…”
Section: Treatment Of Surfacesmentioning
confidence: 99%
“…Some studies have shown that there can be significant sink effects with certain floor and wall covering materials when used in conjunction with other emitting sources highlighting more complex interactions and effects of flooring and wall assemblies including peak VOCs shifts with respect to time instead of simple decays (Won et al 2001). …”
Section: Formaldehyde Emission Behaviormentioning
confidence: 99%